Perbandingan Aktivitas Antibakteri Ekstrak Curcuma zedoaria dan Bahan Irigasi Natrium Hipoklorit 2.5% terhadap Enterococcus faecalis - Martha Mozartha; Prisisilia Silvia; Billy Sujatmiko (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2019)
Sodium hypochlorite (NaOCl) is a powerful disinfectant used in root canal therapy, yet it has some disadvantages. There are growing interests of using extracts of natural materials containing antibacterial secondary metabolite compounds as an alternative of irrigation solution. Aim, to compare the antibacterial activity of white turmeric extracts and 2,5% sodium hypochlorite irrigant against Enterococcus faecalis. Methods, this was a quasi experimental study. White turmeric extracts at the concentrations of 75%, 50%, 25% and 10% were used as experimental groups, while 2,5% NaOCl and distilled water were the control groups. Suspensions of Enterococcus faecalis were prepared to a 0.5 Mc Farland standard and applied onto petri plates containing Muller Hinton Agar. Six wells were created in each plate, and filled with 20 mL of the test solution. Plates were incubated at 37 ° C for 24 hours. The antibacterial activity was evaluated by measuring the clear zone around the well. Data were analyzed by Kruskall Wallis and continued by Mann U Whitney. Results, the largest growth inhibition zones were produced when the test bacteria were in contact with 2,5% NaOCl (15,0233 mm). White turmeric extract 75% concentration had weak antibacterial effect, while white turmeric extract 50%, 25%, 10% concentration, and distilled water did not has antibacterial properties against Enterococcus faecalis. Conclusion, white turmeric extract 75% concentration can inhibit the growth of Enterococcus faecalis with weak antibacterial activity.